Antimicrobial Potential of the Green Microalgae Isolated from the Persian Gulf - Saeed Niazi Vahdati; Hossein Behboudi; Sara Tavakoli; Fatemeh Aminian; Reza Ranjbar (Tehran University of Medical Sciences, 2022)
Background: We aimed to investigate the antibacterial activity of Persian Gulf microalgae extracts on some Gram-positive and negative bacterial species in order to find new compounds with antibacterial activity. Methods: After sampling microalgae from December 2020 to April 2021 from the northernmost part of Qeshm Island in Persian Gulf, the antibacterial activity of methanolic and ethyl acetate extract of microalgae were tested in three concentrations of 125, 250, and 500 mg/ml on Gram-positive bacteria including Staphylococcus aureus, Bacillus cereus, and Gram-negative bacteria including Pseudomonas aeruginosa and Escherichia coli by disk-diffusion assay and the results were compared with two standard antibiotics including ciprofloxacin and streptomycin. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were assessed spectrophotometrically using microplate and enzyme-linked immunosorbent assay (ELISA) reader. Results: Methanolic and ethyl acetate extracts had antibacterial effects against Gram-positive and negative bacteria. Compared to ethyl acetate extract, the methanolic extract showed stronger effects on both Gram-positive and negative bacteria. The most antibacterial effect was related to methanolic extract with a concentration of 500 mg/ml on S. aureus by 14.6 mm inhibition zone. Evidence from MIC also confirmed that the lowest MIC was belonged to methanolic extract by 0.75 mg/ml against S. aureus. Interestingly, both of these extracts showed more antibacterial activity on Gram-positive bacteria than Gram-negative bacteria. Conclusion: The investigation proved the efficacy of microalgae extracts isolated from Persian Gulf as natural antimicrobials and suggested the possibility of employing them in medicines as antimicrobial agents.